Mach Music – Digital & Financial Inclusion in Brazil - Corte Peña, Lourdes Cristina (My University, 2020)
This is a Case Study developed by a group of students of the Universidad Panamericana that took the role of consultants for a Brazilian Start Up. Mach Music, startup created in 2015 is a solution provider in the Telecom Industry for under-served consumers, they seek to venture towards the creation of a business model for the financial and digital inclusion of the unbanked population in Brazil and Latin America. The company is willing to give the market the highest possible financial inclusion through aspirational products or services regarding their real needs until reaching a commercial strategy which could represent a great business opportunity and a spin-out company for them: “Mach Money”. To accomplish that, Mach Music asked consultants to focus on creating a go to market strategy and solidify their credit risk model. Consultants relied on effective analysis tools (decision tree, SWOT) and methodologies (Business Model Canvas & Lean Canvas) to identify what were the real issues of the company. Consultants identified several gaps of information (Business plan), Value proposition, Strategy (segmentation, communication, marketing, etc.) They created an action plan where they suggested Mach Music to start working with the Lean Startup methodology. They gave useful recommendations for the short, mid and long terms and finally, they developed and delivered strategic documentation and designed a website in where Mach Music would be able to manage all their information in a simple way. All these works exceeded Mach Music expectations.
Keywords: CIENCIAS SOCIALES; Gobierno y Economía